Father's involvement in the success of exclusive breastfeeding - Siti Umrana; Ellyani Abadi; Darmayanti Waluyo; Ade Saputra Nasution (AcTion: Aceh Nutrition Journal, 2023)
Breastfeeding is to be the best food that babies should eat because it contains all the nutritional elements needed for growth and development. The role of the father is a factor, one of which can affect the practice of breastfeeding where the role of the father can make the mother feel cared for, calm and this can facilitate milk production. This study aims to see the relationship between the factors of breastfeeding fathers on the practice of breastfeeding. Cross-sectional is a design used in this study which has a sample of 78 fathers who have toddlers taken by random sampling in the Mandonga District, the data obtained were analyzed using the chi-square test. The results of the study showed that there was a relationship between father's knowledge and breastfeeding practice (p= 0,014), attitude variable and breastfeeding practice (p= 0,000) and there was no relationship between father's role and breastfeeding practice p= 0,485). In conclusion, the knowledge and attitudes of breastfeeding fathers are related to the practice of exclusive breastfeeding. There needs to be an increase in father's knowledge of breastfeeding practice support.